(untitled) (Global Journal of Human-Social Science, 2025)
Purpose This study examines how delivery capability which encompasses technical expertise project governance and management practices and organizational agility influences the Public-Private Partnership PPP geothermal energy project completion outcomes in Kenya It is assumed that there is no PPP without either government support or private sector participation rather the issue of utmost research interest would be their effectiveness and or optimization The current research therefore aims to address critical knowledge and research gaps identified in existing literature regarding the operational determinants of PPP project completion in the renewable energy sector particularly geothermal in the Sub- Saharan Africa SSA region Case Study The geothermal industry in Kenya serves as a suitable choice for the case study since the country is globally recognized as a leading geothermal energy developer in Africa Also there is published literature on its geothermal evolution story traceable to the 1980s Research Philosophy Design and Methodology Relying on both the positivist and pragmatic research philosophies mixed methods were used to undertake a cross-sectional census survey of 48 PPP geothermal energy projects licensed in Kenya as of June 2023 A structured questionnaire was used to collect project data from project managers leaders working for both private and public sector developers Responses were measured using an Agree-Disagree A-D Likert scale across the main study themes A key informant interview guide was used to gather qualitative insights from relevant geothermal industry actors including government officials private investors development financing institutions civil society academic and other subject matter experts A pilot study was conducted on a PPP wind power project in Kenya Quantitative project completion metrics were analyzed along with qualitative insights to assess the relative influence of delivery capability on PPP financing structure and project completion A combination of tools was used to analyze descriptive inferential and qualitative data sets culminating in data triangulation